Simultaneous achievement of energy-efficient operation and high thermal stability of magnetic devices by enhancement of Dzyaloshinskii-Moriya interaction and magnetic anisotropy energy - Park, Yong Keun; Kim, Min-Hwan; Kim, Joo-Sung; Nam, Yuneseok; Yu, Ji-Sung; Park, Jung-Hyun; Yoon, Jaesung; Kim, Duck Ho; Choe, Sug-Bong; Min, Byoung Chul (AMER PHYSICAL SOC, 2024)
Energy-efficient operation and stable data retention are the key features of magnetic information devices. Simultaneous achievement of writing-energy reduction and data-stability enhancement has yet faced a dilemma, since both are subjected to the same governing mechanism of magnetization switching, and thus, it is not easy to reduce writing energy while keeping high thermal stability. Here, we propose a solution that bypasses the dilemma by introducing chiral spin alignment in magnetic structures, which assists the current-induced switching at pattern edges, with the energy barrier enhancement. Experiments on asymmetric Pt/Co/Cu/Pt films reveals that both the Dzyaloshinskii-Moriya interaction (DMI) and perpendicular magnetic anisotropy (PMA) are increased by inserting an ultrathin Cu layer. A large PMA enhances the thermal stability, whereas a large DMI reduces the switching current density by tilting the angle of chiral spin alignment at pattern edges. The present observation shows that an effective DMI engineering provides energy-efficient and highly stable magnetic structures suitable for spintronic applications.